2003
DOI: 10.1002/pits.10135
|View full text |Cite
|
Sign up to set email alerts
|

Competence, persistence, and success: The positive psychology of behavioral skill instruction

Abstract: Early school failure is a critical factor in the development of peer rejection and antisocial behavior in children. This paper describes three sets of instructional strategies that have been shown to promote high levels of academic competence by arranging frequent opportunities for correct skill practice: (a) teaching children at their instructional level and monitoring progress, (b) teaching children differently as their skills improve, and (c) rewarding success and setting goals. Research is reviewed showing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
33
0
1

Year Published

2003
2003
2017
2017

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 53 publications
(35 citation statements)
references
References 42 publications
0
33
0
1
Order By: Relevance
“…They also need the support from caregivers that allows them to tolerate failure and persist until they master their goals (Jeon, Peterson, & DeCoster, 2013). These processes lay the foundation for mastery motivation and academic achievement in the school years (Martens & Witt, 2004). Thus, an important question is how individual and dyadic regulatory processes lay the groundwork for the development of mastery motivation that is applied in the school setting.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…They also need the support from caregivers that allows them to tolerate failure and persist until they master their goals (Jeon, Peterson, & DeCoster, 2013). These processes lay the foundation for mastery motivation and academic achievement in the school years (Martens & Witt, 2004). Thus, an important question is how individual and dyadic regulatory processes lay the groundwork for the development of mastery motivation that is applied in the school setting.…”
Section: Discussionmentioning
confidence: 99%
“…Whereas regulatory skills may facilitate mastery motivation, exposure to success is also important in cultivating mastery experiences (Martens & Witt, 2004). Children who are successful at a task tend to persist more at that same task (Maslin-Cole et al, 1993).…”
Section: Introductionmentioning
confidence: 99%
“…Conversely, other researchers discuss the importance of practicing the application of fluent component skills rather than these automatically emerging once fluent (Codding et al, 2010;Martens & Witt, 2004). It has been suggested that two types of practice exist consisting of drills and composite practice (Codding et al, 2010;Cohen et al, 1992;Haring & Eaton, 1978).…”
Section: Discussionmentioning
confidence: 99%
“…The astute reader will no doubt notice that many of the strategies involved in deliberate practice (i.e., a well-sequenced curriculum, direct instruction of component skills, brief repeated opportunities to respond with feedback and reinforcement) are consistent with other domains of behavioral skill training such as adaptive behavior, communication, and basic academic competency (Martens, Daly, Begeny, & VanDerHeyden, in press;Martens & Witt, 2004). A considerable amount of research exists concerning the use of these strategies to improve athletic performance, particularly goal setting, feedback, and public posting (e.g., Koop & Martin, 1983;Mellalieu, Hanton, & O'Brien, 2006;Ward & Carnes, 2002).…”
Section: Developing Fluent Efficient and Automatic Repertoires Of Amentioning
confidence: 99%